2017
DOI: 10.1111/ocr.12146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet‐rich plasma on orthodontic tooth movement in dogs

Abstract: Local injection of PRP in the present animal study resulted in accelerated orthodontic tooth movement with no obvious clinical or microscopic side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 26 publications
5
79
3
Order By: Relevance
“…20 Textor and Tablin 21 showed that calcium chloride activation might be the most inexpensive and effective method, although it might need 20 minutes for activation of PRP. 20 The injection technique in five different areas around the retracted canine followed the same protocol reported by Rashid et al 5 This may be compared with the findings of Gülec et al, 10 who injected the PRP only at the buccal vestibular mucosa adjacent to the mesial root of the first molar. Intraligamentary injection at the distobuccal and distopalatal surfaces of the canine root was advocated in this study based on the work by Von Böhl et al, 22,23 who reported that, as a consequence of local stress and shear concentrations, most hyalinized areas were not found in the area of the central plane but rather lingually and buccally from it.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…20 Textor and Tablin 21 showed that calcium chloride activation might be the most inexpensive and effective method, although it might need 20 minutes for activation of PRP. 20 The injection technique in five different areas around the retracted canine followed the same protocol reported by Rashid et al 5 This may be compared with the findings of Gülec et al, 10 who injected the PRP only at the buccal vestibular mucosa adjacent to the mesial root of the first molar. Intraligamentary injection at the distobuccal and distopalatal surfaces of the canine root was advocated in this study based on the work by Von Böhl et al, 22,23 who reported that, as a consequence of local stress and shear concentrations, most hyalinized areas were not found in the area of the central plane but rather lingually and buccally from it.…”
Section: Discussionmentioning
confidence: 94%
“…24 Conversely, previous studies evaluating the effects of local pharmacologic agent injection to accelerate tooth movement reported only one or two submucosal or gingival injection sites. 4,10,[25][26][27] Injections were delivered every 3 weeks and repeated until the sixth week following the protocol reported by Rashid et al 5 Although the study continued for 4 months, injections were not continued through the whole duration of the study in order to determine whether PRP injections were enough in the initial phases of tooth movement only, as compared with corticotomy 12 or low-level laser therapy applications. 3 The results of the current study showed a faster rate of canine retraction on the intervention side in the first month by 15% and in the second month by 5%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations